2013
DOI: 10.2147/ijn.s41457
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and in vitro and in vivo investigation of chitosan-coated poly (d,l-lactide-co-glycolide) nanoparticles for intestinal delivery of exendin-4

Abstract: Background: Exendin-4 is an incretin mimetic agent approved for type 2 diabetes treatment. However, the required frequent injections restrict its clinical application. Here, the potential use of chitosan-coated poly (d,l-lactide-co-glycolide) (CS-PLGA) nanoparticles was investigated for intestinal delivery of exendin-4. Methods and results: Nanoparticles were prepared using a modified water-oil-water (w/o/w) emulsion solvent-evaporation method, followed by coating with chitosan. The physical properties, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Similar mechanisms occur with chitosan-PLGA NPs, however, due to their positive charge electrostatic interactions occur with the negatively charged cell membrane resulting in a higher P app . The in vivo study revealed higher plasma drug levels and longer retention times of exendin-4 when administered as chitosan-PLGA NP compared to PLGA NP [35]. …”
Section: Drug Release From Chitosan Nanoparticlesmentioning
confidence: 99%
“…Similar mechanisms occur with chitosan-PLGA NPs, however, due to their positive charge electrostatic interactions occur with the negatively charged cell membrane resulting in a higher P app . The in vivo study revealed higher plasma drug levels and longer retention times of exendin-4 when administered as chitosan-PLGA NP compared to PLGA NP [35]. …”
Section: Drug Release From Chitosan Nanoparticlesmentioning
confidence: 99%
“…14,21,[27][28][29]37 The in vivo animal model provided further toxicity information where 3 out of 9 of the in vivo animal model studies indicated partial nontoxic animal effect, one was toxic while the remaining results recommended ENPBCs as a potential candidate for drug therapy with limited information on toxicity (Table S2). Some of the in vivo ENPBCs toxicity effects demonstrated programmed cell death, causing the release of H 2 S. 29 The ENPBCs that exhibited in vivo nontoxic effect were mostly those that had the therapeutic effects of antibody-drug conjugate, 27 CTAB layers of gold for diagnosing rheumatoid arthritis, 30 surface coating polymeric NPs used for inhibiting cancerous cells 31,[38][39][40][41][42][43][44][45][46][47] and felodipine-loaded polymers for pathological examination of different organs of Wister albino mice 50. The ENPBCs with partial nontoxic effect were chitosan-coated polymers for drug delivery, 49 silver NPs coated polymers that were found localized in various body organs, 48 and drug delivery polymeric NPs for anticancer. 51 The findings indicated limited data and information regarding the regulation of ENPBCs toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…These varying outcomes are described in Table S2. 24,28,[30][31]38,[44][45][46][47][48][49][50][51] Altogether, more in vivo animal predictive data are needed to validate standard methods for determining the safe applications of ENPBCs in humans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan (CS) has gained attention in the nanomedicine field because it carries a positive charge that can be utilized for cellular and anatomic targeting of NPs [ 12 ]. The electrostatic interactions between positively charged CS NPs and the negatively charged cell surface have been shown to enhance nanoparticle uptake [ 13 – 18 ]. By using a PLGA core in conjunction with a CS shell, both hydrophobic and hydrophilic drugs can be encapsulated within NP.…”
Section: Introductionmentioning
confidence: 99%